1998
DOI: 10.3354/meps172037
|View full text |Cite
|
Sign up to set email alerts
|

Density, biomass and productivity of animals in four subtidal rocky reef habitats:the importance of small mobile invertebrates

Abstract: Density, biomass and productivity of animals >0.5 mm were estimated in 4 shallow subtidal rocky reef habitats in temperate northeastern New Zealand. The main objective was to determine the relative contributions of mobile epifauna (0 5-10 mm) and megafauna (> 10 mm) to the flux of materials on the reef. The habitats surveyed were (1) Carpophyllum plumosuln var. capillifolium forest (Phaeophyceae: Fucales), (2) Ecklonia radiata forest (Phaeophyceae: Laminariales), (3) urchin barrens, and (4) articulated coralli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
1
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 43 publications
4
102
1
6
Order By: Relevance
“…Crustacean mesograzers are responsible for a major fraction of total secondary production in many vegetated marine systems (Klumpp et al 1989, Taylor 1998, and production by mesograzer prey is the most reliable predictor of production by higher trophic levels (Edgar and Shaw 1995). In our experiment, populations of the amphipod Gammarus grew much more rapidly and produced more biomass than either isopod species did (Figs.…”
Section: Grazer Functional Diversity and Ecosystem Processes In Seagrmentioning
confidence: 51%
See 1 more Smart Citation
“…Crustacean mesograzers are responsible for a major fraction of total secondary production in many vegetated marine systems (Klumpp et al 1989, Taylor 1998, and production by mesograzer prey is the most reliable predictor of production by higher trophic levels (Edgar and Shaw 1995). In our experiment, populations of the amphipod Gammarus grew much more rapidly and produced more biomass than either isopod species did (Figs.…”
Section: Grazer Functional Diversity and Ecosystem Processes In Seagrmentioning
confidence: 51%
“…In addition to their top-down grazing effects on plants, the small crustaceans that dominate herbivore guilds in many estuarine and coastal marine ecosystems also play an important role in nutrient cycling (Taylor and Rees 1998), and they are critical links in the food chain to higher trophic levels. Their production often regulates population size and production of fishes (Kikuchi 1974, Edgar and Moore 1986, Edgar and Shaw 1995, Taylor 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of secondary production have been used to improve the understanding of important ecological issues such as energy transfer within communities, monitoring of benthic communities (Wilber and Clarke 1998), rational management of aquatic resources (Downing 1984), and food web analyses (Benke 1998). Moreover, measures of production are informative because they represent the rate at which organic matter is made available to higher trophic levels and reflect the relative importance of organisms as consumers and nutrient recyclers (Taylor 1998). …”
Section: Introductionmentioning
confidence: 99%
“…taxonomic measurements of diversity suggested sponge flats were more diverse than traditional indices (S, H', l-X, Nl, N2) would otherwise infer. Previous studies have shown that differences in diversity between habitats could be owing to varying levels of structural complexity (Mora et al 2003;Anderson & Millar 2004) and productivity (Taylor 1998;Babcock et al 1999), although these factors were not quantified in the present study.…”
Section: Discussionmentioning
confidence: 85%